Implementing Halal Industry Management and Environment Conservation Based on Maqashid Sharia - Ahmad Erwaedy; Pardiman Pardiman; Syahril Syahril; Ach. Andiriyanto (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: Ecosystem problems are an increasingly complex and serious global problem faced by human beings around the world. More and more production with the use of modern technology to exploit nature continuously resulted in the declining quality of the environment. The core of a green economy is low carbon growth, resource efficiency, and social inclusivity, which have implications for sustainable development, energy management, a green economy in urban areas, as well as green business. This is in accordance with the values in Islamic economics, especially analyzed from the Maqashidal-Shariah point of view. This study intended to give an overview of halal industry management and environment conservation in the view of Maqashid ShariaDesign: This study was a literature study to overview the management of halal industry and environment conservation in the view of Maqashid Sharia.Findings: Economic dissemination with the universal values of Maqashid Sharia (linking environmental issues with aspects of sharia objectives) in fiqh al-bi'ah resulted in a decrease in the passive attitude of the community. The basis of the green economy on the problem of inequality caused by the unequal distribution of green production factors can be overcome based on the principles of al-adl (justice), Maslahah (public interest) and Musawah (equality).Originality/Values: Various obstacles that arise will be overcome because the purpose of Sharia is a concept based on the guidelines set by the Creator.